Arctic Resilience: No Evidence of Vegetation Change in Response to Grazing and Climate Changes in South Greenland. Issue 2 (1st August 2016) - Damgaard, Christian; Raundrup, Katrine; Aastrup, Peter; Langen, Peter L.; Feilberg, Jon; Nabe-Nielsen, Jacob
ABSTRACT: Recent studies suggest that climate changes may have a strong impact on the vegetation composition in Arctic ecosystems, causing increasing dominance of woody species. Evidence from short-term studies on the effects of herbivory indicates that this effect may be counteracted by grazing, but it has not yet been studied whether the effect is persistent and general. Here, we present the results from a large-scale, long-term study of the effects of sheep grazing and climate on the relative dominance of woody plants, graminoids, and forbs. The study is based on exclosures established from 1984 onward across a climatic gradient in South Greenland. The relative cover of the three plant functional types was modeled in a state-space model. There was no significant overall change in the relative cover of the three groups, although such changes occurred intermittently on some sites. This suggests that the relative dominance of the plant functional types is resilient to the impacts of grazing and climate changes in the tundra of South Greenland in line with other studies from sites where summer temperatures have not increased.